Conspirituality: Predicting COVID-19 Conspiracy Beliefs Using, Spirituality, Purity, and Political Orientation - Schofield, Malcolm; Howard, Chris; Rimmer, Stu (Journal of Scientific Exploration, 2026)
Conspirituality refers to the link between spirituality and the belief in conspiracy theories. This has been linked to the new age and wellness movement, and specifically, COVID-19 conspiracy theories surrounding the vaccine. This study aimed to be one of the first to conduct an empirical study exploring the validity of the term conspirituality and some other variables that might explain this relationship. In this case, moral purity and political orientation. An online survey recruited 240 participants via social media. COVID-19 and general conspiracy theories, political orientation, and spirituality were measured using individual scales; moral purity was measured via a subscale of the Moral Foundations Questionnaire. A multiple regression found that spirituality, purity, and political orientation (right-wing) significantly predicted COVID-19 conspiracy theory belief. Further investigation found that moral purity and political orientation mediated the relationship between COVID-19 conspiracy and general conspiracy theory beliefs, except for political orientation, which was not a mediator between spirituality and general conspiracy beliefs. The network analysis confirmed that political orientation and purity are at the model’s centre. In conclusion, conspirituality is a valid term and potentially contributesto anti vaccination sentiments. However, this study shows that moral purity and political orientation are key variables when explaining the relationship between spirituality and conspiracy belief.